Fatini Nasuha’s Leadership and Volunteering Dedication Recognised at MARS 2023 Awards - Nor Azlina, Ahmad (UMPSA, 2024)
KUANTAN, 18 May 2024 – Fatini Nasuha Ahmad Puad, a student of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) was named the Promising Student Figure at the 2023 Mercu Sanjungan Award (MARS) Ceremony held at Zenith Hotel, Kuantan recently.